Transformasi Perilaku Keuangan Digital: Studi QRIS dan Literasi Keuangan dalam Perspektif Islam - intan Suri Mahardika Pertiwi (Perbanas Journal of Islamic Economics and Business, 2026)
The accelerating growth of financial technology has reshaped public financial behavior toward digital ecosystems, yet this shift has not been proportionally matched by sufficient financial literacy among users. This study evaluates the contribution of Quick Response Code Indonesian Standard and financial literacy in shaping digital financial behavior transformation through the lens of Islamic financial management, employing a quantitative survey design with 100 digital wallet users in Bandar Lampung selected via the Lemeshow formula and analyzed using multiple linear regression. Findings reveal that QRIS adoption yields no meaningful positive impact on digital financial behavior transformation, as users predominantly treat the technology as a transactional convenience rather than a catalyst for substantive financial change. Financial literacy, conversely, emerges as the dominant predictor with a positive and significant influence in cultivating more deliberate, systematic, and accountable digital financial behavior. The distinctiveness of this study lies in unifying digital payment technology, financial literacy, and financial behavior within an Islamic financial management framework in a local setting, with strategic implications underscoring the necessity of strengthening payment ecosystems alongside sharia-grounded financial literacy initiatives